Bioecology Of David’s Buddleia (Buddleia Davidii), Breeding Technology (Texas Journal of Agriculture and Biological Sciences, 2024)
Buddleja davidii is a widespread shrub in Asia. To explore whether floral volatiles, morphological characters of flower and seed and breeding system are correlated with their distributions, we measured length and width of corolla, trichome density at corolla throat, level of stigma/anthers relationship, seed size and weight. The results indicated that these characteristics were significantly different between the two species (P < 0.01).